Pengunaan Iklan Media Massa Universitas Komputer Indonesia (UNIKOM) Dengan Pengambilan Keputusan Mahasiswa Baru Tahun 2019 - Arief Nurul Wasim; Evi Novianti; Yustikasari - (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2022)
This research is entitled "The Use of Mass Media Advertising at the University Computer Indonesia (UNIKOM) with Decision Making for New Students in 2019". This research is motivated by the existence of a gap between the use of mass media advertising and student decision making. The formulation of the problem of this research is "How is the Relationship between the Use of Mass Media Advertising by the Indonesian Computer University (UNIKOM) and the Decision Making for New Students in 2019". This study aims to determine whether there is a relationship between the intensity of media use, the content of mass media advertising messages, and the relationship between individuals and the content of messages with the fulfillment of information needs and knowledge of information. This study uses the theory of Uses and Gratifications with correlational methods and descriptive and inferential data analysis techniques. The number of samples was 95 respondents who were determined through simple random sampling technique. Data collection was done by distributing questionnaires, observations, interviews and literature studies. The results of this study state that there is a significant and significant relationship between the use of mass media advertisements by UNIKOM and student decision making.